The study of fuel mixtures with palm oil. (November 2019) - Oshchepkov, P P; Smirnov, S V; Zaev, I A; Vorobyev, A A
Abstract: The search for alternative fuels for heat engines is an urgent task for scientists around the world. For diesel engines, vegetable oils seem to be the most promising. The use of a partial addition of vegetable oils to diesel fuel allows us to reduce the consumption of hydrocarbons and not cause significant changes in the design of the engine, as well as affect the composition of the exhaust gases. For countries producing palm oil, including Nigeria, this method is economically viable. This article presents the results of computational studies of the features of the combustion process of biodiesel fuel with additives of palm oil and hydrogen peroxide and the effect of additives on the ignition delay period and the combustion process. The calculations have shown the effectiveness of using hydrogen peroxide as an additive to the biofuel under consideration to reduce the ignition delay period and, consequently, improve the power and economic indicators.